APLIKASI TERAPI BERMAIN SEBAGAI INTERVENSI DISTRAKSI PADA ANAK DENGAN PROSEDUR PEMBEDAHAN - sholihatul amaliya; Rinik Eko kapti; Septi Dewi Rachmawati; Nurona Azizah (Caring : Jurnal Pengabdian Masyarakat, 2021)
Hospitalization is one of the events that affects the child’s development, one of which is caused by surgical procedures. Surgical procedures can cause anxiety (pre-surgery) and pain (post-surgery). Play therapy is a non-pharmacological method that can reduce children's pain and anxiety levels. This community service activity aims to implement play therapy as a distraction intervention so that it can reduce children's pain and anxiety. This activity was attended by 21 children who will and have undergone surgical procedures in the Rinjani room at the Dr. Saiful Anwar Malang hospital in January 2020. Play therapy activities are divided into two parts, single and associative play therapy where the form of games given was adjusted to the child's age group. The children's pain and anxiety level was measured before and after intervention using a visual analogue scale (VAS) and the data were analyzed using a paired t-test with a significance level of α <0.05. The results of the activity showed a significant difference in the level of pain in children before and after playing therapy where after playing therapy there was a decrease in the level of pain. Play therapy activities are effective to be applied as a non-pharmacological method for children who are undergoing surgical procedures.